Fenomena Erologi Jepang-Indonesia pada Mahasiswa Bahasa Jepang Tahap Menengah di Universitas Indonesia - Tjandra, Sheddy N (UI Scholars Hub, 2004)
Errology is a term launched by Prof. Mineo Suenobu (1995-1999) that means study of error analysis. JapaneseIndonesian errology is a study of various errors done by Indonesian students in learning Japanese as a a foreign language. The intermediate course in this research is a Japanese class from third grade students at Department of Japanese Studies, Faculty of Humanities. Therefore, the Japanese-Indonesian errology in this research is about the errors from early intermediate Japanese, Intermediate Japanese is a level of foreigner’s Japanese who has learned hiragana, katakana, 300 Chinese characters, 1500 words and basic grammar. This competence reached about 1000 Chinese characters, 6000 words and some advanced grammatical categories. From language acquisition, there are two kind of errors: (1) interlingual errors, caused by the students’ mother tongue; (2) intralingual errors, caused by the structural problems of Japanese language. Interlingual errors are much more than intralingual errors. From the structure of language, there are six kind of errors: (1) grammatical errors; (2) lexical errors; (3) pragmatic errors; (4) lexicalpragmatic errors; (5) lexical grammatical errors; (6) grammatical-pragmatic errors. Grammatical errors are the most.